2005
DOI: 10.1002/art.21366
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow abnormalities on magnetic resonance imaging are associated with type II collagen degradation in knee osteoarthritis: A three‐month longitudinal study

Abstract: Objective. Using radiography to assess the efficacy of a disease-modifying osteoarthritis (OA) drug on joint structure is challenging. Subchondral bone marrow abnormalities determined by magnetic resonance imaging (MRI) and urinary excretion of C-terminal crosslinking telopeptide of type II collagen (CTX-II) have recently been shown to be predictors of radiographic progression in patients with knee OA, suggesting that these may represent valuable biomarkers with increased sensitivity compared with findings on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
4
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 27 publications
4
90
4
8
Order By: Relevance
“…Another limitation of our study is that we did not study the resolution of pain, but rather its increase. We have previously reported that BMLs are unlikely to disappear in knees with OA, but rather, BMLs often tend to either increase or appear over time (24,25), and this has been confirmed by other investigators (26). We therefore did not believe that it would be productive to focus on the resolution of pain and its association with the resolution of BMLs, since little such resolution occurs.…”
Section: Discussionmentioning
confidence: 67%
“…Another limitation of our study is that we did not study the resolution of pain, but rather its increase. We have previously reported that BMLs are unlikely to disappear in knees with OA, but rather, BMLs often tend to either increase or appear over time (24,25), and this has been confirmed by other investigators (26). We therefore did not believe that it would be productive to focus on the resolution of pain and its association with the resolution of BMLs, since little such resolution occurs.…”
Section: Discussionmentioning
confidence: 67%
“…Histologically, BMLs represent multiple abnormalities, including osteonecrosis, trabecular abnormalities, and bone remodeling, but rarely edema (17). BMLs may also be caused by inflammation in reaction to cartilage breakdown products or other factors in intruded synovial fluid (18). However, thus far, whether inflammation is associated with BMLs in OA patients is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following 40 patients with knee OA, Phan et al [17] reported both decreases and increases in BML score (graded from 0 to 3 with 3 as severe) from baseline after one or 2-year follow-up. Evaluating 377 patients with painful knee OA, Garnero et al [22] reported that within 3 months, BML scores (as defined before) decreased in 37 patients and increased in 71. Assessing 182 patients with OA at baseline and at 2-year follow-up, Kornaat et al reported that total size of BML changed in 66% patients, with change in size of individual lesions as 45%, new lesions appeared in 21%, and existing lesions completely disappeared in 10% [23].…”
Section: Natural History and Pathophysiology Of Bml In Oamentioning
confidence: 97%